Hubungan Sikap Dan Pengetahuan Ibu Terhadap Kejadian Stunting Pada Anak Usia 1-5 Tahun - Purbanova, Reni; Astri Retno Widiati (Jurnal Ilmiah Kesehatan Delima, 2025)
Stunting is a condition in which a child experiences growth disturbances so that the child's height does not match his age, as a result of chronic nutritional problems, namely lack of nutritional intake for a long time. Stunting is not only caused by one factor but from various interrelated factors. Among them is the parenting style of parents, the role of parents, especially mothers, is very important in meeting the nutritional needs of children because to provide good nutrition, a level of knowledge is needed in food selection. To determine the relationship between mother's attitude and knowledge of stunting in children aged 1-5 years.This research is a quantitative research with descriptive research criteria through a cross sectional approach.From the results of multivariate testing with multiple correlation tests, it was found that the probability value (sig.F.change) = 0.000 was obtained. Because the sig.F.change value is 0.000 <0.05, there is a simultaneous and significant relationship between Mother's Attitudes and Knowledge of Stunting Incidents in children aged 1-5 years at the Ngudi Lestari Posyandu